2011
DOI: 10.1088/0004-637x/733/1/38
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Properties of Delta Scuti Stars Using Spectroscopic Eclipsing Binary Systems

Abstract: Many stars exhibit stellar pulsations, favoring them for asteroseismic analyses. Interpreting the oscillations requires some knowledge of the oscillation mode geometry (spherical degree, radial and azimuthal orders). The δ Scuti stars (1.5 -2.5 M ⊙ ) often show just one or few pulsation frequencies.Although this may promise a successful seismological analysis, we may not know enough about either the mode or the star to use the oscillation frequency to improve the determination of the stellar model, or probe th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…We assume that the model behaves linearly locally, and so we can use a simple inversion method to calculate the parameter changes (dP) to make to an initial guess of the parameters P 0 in order to bring the model observables into line with the simulated observations, see Creevey et al (2011). (This involves calculating the Jacobian matrix dF/dP evaluated at the solution, where F are the observables, such as luminosity ratio and frequency ratios.)…”
Section: Grid Model and Frequency Ratios (Creevey)mentioning
confidence: 99%
“…We assume that the model behaves linearly locally, and so we can use a simple inversion method to calculate the parameter changes (dP) to make to an initial guess of the parameters P 0 in order to bring the model observables into line with the simulated observations, see Creevey et al (2011). (This involves calculating the Jacobian matrix dF/dP evaluated at the solution, where F are the observables, such as luminosity ratio and frequency ratios.)…”
Section: Grid Model and Frequency Ratios (Creevey)mentioning
confidence: 99%
“…Classical pulsators in eclipsing binary stars offer the possibility to alleviate this problem. Creevey et al (2011) found that eclipsing binaries constrain fundamental properties of a star equally well or better than what is possible for a pulsating δ Scuti star with correct mode identification ( Figure 4). Conversely, the correct mode identification can be inferred by comparing solutions assuming different mode identifications, and identifying those solutions which yield the best match to the binary constraints.…”
Section: Mode Identification and Driving Mechanisms In Intermediate Mmentioning
confidence: 74%
“…Dashed lines mark the exact input solution, the box show the initial guess values, and the error bar mark the input uncertainties for the eclipsing binary solution. From Creevey et al (2011).…”
Section: Mode Identification and Driving Mechanisms In Intermediate M...mentioning
confidence: 99%
“…The promise of working on δ Scuti stars in EBs is the possibility to perform mode identification, enabled by precise knowledge of the mass and radius of the pulsating star [14]. This is notoriously tricky to achieve, but would specify precise constraints on stellar theory.…”
Section: δ Scuti Stars In Eclipsing Binariesmentioning
confidence: 99%